Improving transition domains by examining self-determination proficiency among gender and race of secondary adolescents with specific learning disabilities - Garrett, Barbara A. (Kansas State University, 2010)
Secondary adolescents with disabilities (AWD) have been mandated participants in their Individual Education Plan (IEP) and Individual Transition Plan (ITP) meetings since 1990, yet overprotective and well-meaning adults have assumed their advocacy role (Janiga & Costenbader, 2002). This has weakened their (secondary AWD) ability to become self-determined. Secondary AWD should be involved with the development, implementation and execution of services and supports in their IEP/ITP in order to benefit from their participation in general education as well as develop self-determination skills. To improve transition outcomes, this study examined self-determination and socio-cultural factors (race/ethnic and gender groups) among secondary adolescents with disabilities by differentiating baseline skills among race and gender groups. The two independent variables were race/ethnicity and gender. The dependent variables were the self-determination total score and each of four domain total scores (Autonomy, Self-Regulation, Psychological Empowerment, and Self-Realization) of the Arc’s Self-Determination Scale. The literature revealed that there was not a standard for self-determination training programs for students with disabilities and teachers (Brunello-Prudencio, 2001). However, empirical data has emphasized that socio-cultural development (i.e. gender and race) could impact self-determination. Understanding the socio-cultural perspective of race/ethnicity and gender on self-determination has the potential to improve transition practices as well as highlight the importance for self-determination (Trainor, 2005). This study utilized information from the Arc’s Self-Determination Scale (Wehmeyer & Kelchner, 1995) score of secondary adolescents with disabilities to determine whether differences existed among race/ethnic and gender groups. Research findings from this study indicated significant differences in total scores among race/ethnic groups for: (1) the autonomy domain (the ability to express personal preferences or beliefs); (2) self-determination; and (3) there was no significant difference for gender on either domain score or self-determination total scores. This research revealed that a self-determination assessment instrument could be used to isolate essential abilities and behaviors by gender and race for secondary adolescents with disabilities. To promote positive outcomes among deficit areas of self-determination for secondary adolescents with disabilities, this researcher recommended differentiated strategies for educational practitioners. Differentiated strategies could focus on collaborative learning communities, experiential learning options, and reduced emphasis on competitive learning environments.
Keywords: Improving Adolescent Transition Services Race Gender; Education, Special (0529)